Ultrasonic phased array flexible coupling detection of defects in high-voltage cable terminal lead seals - Ziping, Peng; Jishi, Zheng; Zhiming, Zhen; Yaosheng, Huang; Xiaobin, Li; Qiushen, Cai (Frontiers in Mechanical Engineering, 2025)
High-voltage cable terminal lead seals may develop defects such as holes, cracks, or delamination due to substandard installation quality or external forces during operation. Owing to the large curvature of the lead seal surface, using conventional ultrasonic probes for direct contact with the surface results in low efficiency in detecting lead seal defects and yields a low signal-to-noise ratio for defect echo signals. To address the ineffective detection of lead seal defects, a non-destructive detection method based on ultrasonic phased array flexible water bag coupling is proposed. This method employs an ultrasonic phased array probe and a flexible water bag coupling device to form a lead seal defect detection system. Firstly, a simulation model for lead seal defects is established using COMSOL finite element simulation software to design and optimize the detection parameters of the ultrasonic phased array probe. Detection experiments are then conducted on three typical artificially fabricated defect samples. The results indicate that different beam deflection angles and focal distances of the probe affect the detection outcomes. Through ultrasonic phased array probe sector scan (S-scan) images and ultrasonic pulse echo reflection (A-scan) images, both qualitative analysis and quantitative measurement of lead seal defects can be achieved. This method demonstrates that the ultrasonic phased array terminal lead seal defect detection technique, utilizing a flexible water bladder coupled probe, can quickly and intuitively identify lead seal defects, providing a new approach for defect detection in high-voltage cable terminal lead seals.